Pertanggung Jawaban Pidana Pelaku Tindak Pidana Perampokan Dikabupaten Muara Enim Analisis Putusan No 137/PID.B/2018/PN MRE - Dunan, Hendri; Yusuf, Hambali; Okpirianti, Reni (Universitas Semarang, 2025)
This research was conducted in Muara Enima District, South Sumatra. This research aims to explain what causal factors are the reasons for acts of violence against women. Explaining the forms of crime that occurred in cases in the Tanjong Terang Muara Enim village area. Explain the impact felt by the victims of robbery and allowing accidents to occur. The method used in this research is the Normative Juridical research method, Data Collection Techniques in legal research using Library Research. Based on the results of the research, basically the defendant has carried out legal responsibility for the defendant's sentence, in this case the defendant was punished under Article 365, but the sentence for the defendant was too light considering Article 365 paragraphs 1 and 2 of the existence of an aggravating crime which means the defendant must be sentenced longer. again, namely more than two years and eight months according to the judge's decision. The judge's consideration in this case is only on material losses by the victim, without considering that the criminal committed two criminal acts at once, which basically does not have an alternative charge there, but can be punished with two crimes at once. Keywords: Criminal, Criminal, Robbery.